End of induction patient reported outcomes predict clinical remission and endoscopic improvement with vedolizumab and adalimumab in ulcerative colitis. (2nd January 2023) - Wong, Emily Chu Lee; Hasan, Badar; Dulai, Parambir S.; Marshall, John K.; Reinisch, Walter; Narula, Neeraj
Abstract: Background: Patient-reported outcomes (PROs) are increasingly emphasized as endpoints in clinical trials of ulcerative colitis (UC). However, the prognostic value of early improvement in PROs for long-term outcomes remains unclear. Methods: This was a post-hoc analysis of 611 vedolizumab-treated or adalimumab-treated patients in the VARSITY trial (Clinicaltrial.gov: NCT02497469). Stool frequency (SF) and rectal bleeding score (RBS) as reported in the Mayo score at post-induction (week 6 and 14) was assessed for their association with one-year endoscopic improvement (EI), defined as Mayo endoscopic subscore <2; histo-endoscopic mucosal improvement (HEMI), defined as EI and Geboes highest grade <3.2, clinical remission (CR), defined as total Mayo score ≤2; and PRO-2 remission, defined as RBS of 0 and SF ≤1. Multivariable logistic regression models adjusted for confounders assessed the relationships between post-induction PROs and outcomes of interest at one-year. Results: Patients with severe SF at week 6 were significantly less likely to achieve one-year EI compared to those with non-severe SF [aOR 0.40 (95% CI: 0.24–0.68), p < .001]. Absence of rectal bleeding at week 6 was associated with greater odds of achieving EI at one-year [aOR 2.21 (95% CI: 1.58–3.09), p < .001]. These findings were consistent across comparisons at week 14. Similar findings were observed for the outcomes of one-year HEMI, CR and PRO-2 remission. No difference was observed between the modified partial Mayo score and modified PRO-2 score. Conclusions: Post-induction PROs strongly predict the odds of CR and EI in UC and simplified evaluations can be used to assess early response to UC therapies.